Application of sigma-based quality control rules for the efficiency of internal quality control - Choi, Hyunji; Jeong, Ina; Cheon, Jeongeun; Park, Chul-Min; Lee, Sun Min (Practical laboratory medicine, 2025)
Ensuring stability in medical laboratories through quality control (QC) is crucial and requires fitted rules to prevent false alerts and identify errors. This study demonstrates how the introduction of new QC rules to align with individual total allowable error (TEa) affects laboratory efficiency and error detection. Changes in the performance of 26 biochemical tests before and after applying new internal quality control (IQC) rules were studied. Pre-Phase utilized uniform QC rules (1–3s, 2-2s, 2/3-2s, R-4s, 4-1s, and 12-x) while Post-Phase adopted new QC rules selected using Westgard Adviser (Bio-Rad Inc., USA). Sigma metrics were calculated using TEa and precision and bias from IQC data, compared to the peer group. Efficiency was assessed by comparing QC-repeat rates, turnaround times (TAT), and proficiency test (PT) results. QC-repeats due to violations averaged 5.6 % in the Pre-Phase and decreased to 2.5 % in the Post-Phase. As a result, the rate of out-of-TAT in peak-time decreased from 29.4 % to 15.2 %. In Pre-Phase, 67 of 271 cases exceeded the 2 standard deviation index (SDI) in the PT, which was reduced to 24 cases in Post-Phase. Cases exceeding the 3 SDI significantly decreased from 27 to 4 in the Post-Phase. The introduction of sigma-based rules in the internal quality control process improved laboratory efficiency by reducing QC-repeat, recalibration, and TAT while maintaining quality, demonstrating a valuable balance between efficiency and analytical performance. [Display omitted]